Nuclear Power Plants event classification based on International Reporting System (IRS) - Richard Brandão Nogueira Vital; Jefferson Borges Araujo; Tatiane Melo Vital (Brazilian Journal of Radiation Sciences, 2021)
The exchange of information between several business activities can lead to an increase in productivity and quality. In nuclear area, besides economic benefits, the operating experience exchanged can increase of the safety level of nuclear installations. Thus, it´s necessary to evaluate frequently operational occurrences from different countries and companies to learn with their lessons learned to prevent a recurrent events or unexpected consequences.  Because this, several methodologies are recommended to investigate events in an adequate level of depth and perform reports based on local requirements. Generally, these reports contain plant conditions before and after an event occurs (operation mode, operation limits and condition, date and time, nuclear and electrical power) and their information (failure discovery methods, impact to the safety, classification from INES and national regulation scale, similar events, relation to human factors, activation of emergency plan, recommended actions, root cause and causal factors). To allow the exchange of experience the Nuclear Energy Agency (NEA) and International Atomic Energy Agency (IAEA) maintain an Incident Reporting System (IRS) that permits interaction of several member states. In this system, a local coordinator collects information of the most relevant operating events and performs an evaluation of them based on IRS Guideline presented in an annual meeting. This paper evaluates a set of approximately four hundred events reported in IRS between 2014 and 2018. This evaluation has the objective of identify the most recurrent event root causes, operation mode and the effectiveness of corrective actions in course in the nuclear industry.